Comparison of Antibacterial Properties of Nano TiO2 and ZnO Particle Filled Polymers - Altan, M.; Yildirim, H. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
Antibacterial property for the plastic products is very important due to their wide spread usage in many areas close to human health such as a child toy or a food package. There are some methods to make polymers antibacterial such as ionizing radiation but they can be still infected by micro organisms during usage of them. The best and easy way to obtain antibacterial polymers is melt mixing of polymers with antibacterial agents. In this study, nano TiO2 and ZnO particles were mixed with polypropylene and high density polyethylene with a twin screw extruder. Silane was applied to the particles prior melt mixing in order to prevent agglomeration and FT-IR analysis was done to characterize the particles. After melt mixing, particle filled rectangular plates were obtained by plastic injection molding and antibacterial tests were done on the plates according to a standard method, JIS Z 2801. According to the results, satisfactory antibacterial properties were obtained for both polymers and it has been seen that particles without silane could not provide antibacterial effect.
Keywords: ESCHERICHIA-COLI; NANOPARTICLES; Physics